Management of thin endometrium in assisted reproduction: a clinical practice guideline from the Canadian Fertility and Andrology Society. Issue 1 (July 2019) - Liu, Kimberly E.; Hartman, Michael; Hartman, Alex
Abstract: The impact and management of thin endometrium is a common challenge for patients undergoing assisted reproduction. The objective of this Canadian Fertility and Andrology Society (CFAS) guideline is to provide evidence-based recommendations using the GRADE (Grading of Recommendations, Assessment, Development and Evaluations) framework on the assessment, impact and management of thin endometrium in assisted reproduction. The effect of endometrial thickness on pregnancy and live birth outcomes in ovarian stimulation and IVF (fresh and frozen cycles) is addressed. In addition, recommendations on the use of adjuvants to improve endometrial thickness and pregnancy outcomes are provided.